Rituximab Therapy in the Treatment of Juvenile Myasthenia Gravis: The French Experience. (7th June 2022) - Molimard, Agathe; Gitiaux, Cyril; Barnerias, Christine; Audic, Frédérique; Isapof, Arnaud; Walther-Louvier, Ulrike; Cances, Claude; Espil-Taris, Caroline; Davion, Jean-Baptiste; Quijano-Roy, Susana; Grisel, Coraline; Chabrol, Brigitte; et al.
Abstract : Background and Objectives: Corticosteroids are the first-line immunosuppressants in the management of juvenile myasthenia gravis despite their adverse effects. The place of new immunosuppressive therapies is not clearly defined by the last international consensus held in March 2019 due to the lack of clinical trials. The aim of this study is to describe the use of rituximab and its efficacy and safety in 8 main pediatric centers of the French neuromuscular reference network to propose a new place in the therapeutic strategy of juvenile myasthenia gravis. Methods: We conducted a retrospective multicenter study from January 1, 2009, to April 30, 2020, including a large cohort of children with myasthenia gravis in 8 main French pediatric reference centers of the FILNEMUS network. The type of myasthenia, different lines of immunosuppressive treatment, and clinical course of the patients were collected. To evaluate the efficacy of rituximab, we studied the clinical course of patients on immunosuppressive therapy. Outcome was defined as the clinical and therapeutic status of patients at the last visit: stable without immunosuppressants, stable with immunosuppressants, or unstable. Results: We included 74 patients: 18 children with ocular form and 56 children with generalized form. Of the 37 patients who required immunosuppressive therapy, 27 were treated with rituximab. Patients treated with rituximab had a better outcome than patients treated with conventional immunosuppressants ( p = 0.006). The use of rituximab as a first-line immunosuppressant showed a better efficacy with a discontinuation of immunosuppressants in 75% of patients (vs 25%, p = 0.04) and results in cortisone sparing (42% vs 92%, p = 0.03) compared with rituximab treatment as a second- or third-line immunosuppression. Rituximab was well tolerated; no adverse effect was observed. Discussion: The use of rituximab has increased in France over the last 10 years as a first-line immunosuppressant. This study suggests good tolerability and efficacy of rituximab in juvenile myasthenia gravis. Early use appears to improve outcomes and facilitate cortisone sparing in antibody-positive generalized juvenile myasthenia. Classification of Evidence: This study provides Class III evidence that for children with MG, rituximab is effective and well tolerated.